Impacted Compound Odontoma in a 13-year-old Child: A Case Report - Malla, Manisha; Limbu, Senchhema; Dikshit, Parajeeta; Shivakotee, Satyapriya (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Odontomas are considered the most common, asymptomatic odontogenic tumors. They are generally found on routine radiographic examination. However, signs and symptoms relating to their presence may occur. It is commonly associated with retained or impacted deciduous teeth, impaction of permanent teeth, and displacement of teeth. The radiographic examination (intraoral periapical, panoramic radiographic as well as cone beam computed tomography (CBCT) enables the identification, thereby ensuring early management. This case reports surgical management of odontoma under local anesthesia with ground sectioning revealing a compound odontome.